Aberrant Activation of the Hedgehog Signaling Pathway in Malignant Hematological Neoplasms - Chi Young Ok; Rajesh R. Singh; Francisco Vega (2011)
The hedgehog (HH) signaling pathway is a highly regulated signaling pathway that is important not only for embryonic development, tissue patterning, and organogenesis but also for tissue repair and the maintenance of stem cells in adult tissues. In the adult hematopoietic system, HH signaling regulates intrathymic T-cell development, and it is one of the survival signals provided by follicular dendritic cells to prevent apoptosis in germinal center B cells. HH signaling is required for primitive hematopoiesis; however, conflicting data have been reported regarding the role of the HH pathway in adult hematopoiesis. Inappropriate activation of the HH signaling pathway occurs in several human cancers, including hematological neoplasms. Emerging data demonstrate abnormal HH pathway activation in chronic lymphocytic leukemia/small lymphocytic lymphoma, plasma cell myeloma, mantle cell lymphoma, diffuse large B-cell lymphoma, ALK-positive anaplastic large cell lymphoma, chronic myelogenous leukemia, and acute leukemias. In these neoplasms, HH signaling promotes proliferation and survival, contributes to the maintenance of cancer stem cells, and enhances tolerance or resistance to chemotherapeutic agents. Here, we review current understanding of HH signaling, its role in the pathobiology of hematological malignancies, and its potential as a therapeutic target to treat malignant hematological neoplasms. The hedgehog (HH) signaling pathway is a highly regulated signaling pathway that is important not only for embryonic development, tissue patterning, and organogenesis but also for tissue repair and the maintenance of stem cells in adult tissues. In the adult hematopoietic system, HH signaling regulates intrathymic T-cell development, and it is one of the survival signals provided by follicular dendritic cells to prevent apoptosis in germinal center B cells. HH signaling is required for primitive hematopoiesis; however, conflicting data have been reported regarding the role of the HH pathway in adult hematopoiesis. Inappropriate activation of the HH signaling pathway occurs in several human cancers, including hematological neoplasms. Emerging data demonstrate abnormal HH pathway activation in chronic lymphocytic leukemia/small lymphocytic lymphoma, plasma cell myeloma, mantle cell lymphoma, diffuse large B-cell lymphoma, ALK-positive anaplastic large cell lymphoma, chronic myelogenous leukemia, and acute leukemias. In these neoplasms, HH signaling promotes proliferation and survival, contributes to the maintenance of cancer stem cells, and enhances tolerance or resistance to chemotherapeutic agents. Here, we review current understanding of HH signaling, its role in the pathobiology of hematological malignancies, and its potential as a therapeutic target to treat malignant hematological neoplasms. Hedgehog (HH) proteins were first identified in Drosophila as secreted signaling proteins1Nüsslein-Volhard C. Wieschaus E. Mutations affecting segment number and polarity in Drosophila.Nature. 1980; 287: 795-801Crossref PubMed Google Scholar that have an essential role in embryonic development, determining the anteroposterior orientation of developing structures in the Drosophila embryo and larva.2Lee J.J. von Kessler D.P. Parks S. Beachy P.A. Secretion and localized transcription suggest a role in positional signaling for products of the segmentation gene hedgehog.Cell. 1992; 71: 33-50Abstract Full Text PDF PubMed Scopus (480) Google Scholar There is a single Hh gene in Drosophila, but three homologs have been found in vertebrates: sonic hedgehog (SHH), Indian hedgehog (IHH), and desert hedgehog (DHH).3Echelard Y. Epstein D.J. St-Jacques B. Shen L. Mohler J. McMahon J.A. McMahon A.P. Sonic hedgehog, a member of a family of putative signaling molecules, is implicated in the regulation of CNS polarity.Cell. 1993; 75: 1417-1430Abstract Full Text PDF PubMed Scopus (1811) Google Scholar Notably, the three HH ligands activate the same signal transduction pathway, but they regulate different organ systems.3Echelard Y. Epstein D.J. St-Jacques B. Shen L. Mohler J. McMahon J.A. McMahon A.P. Sonic hedgehog, a member of a family of putative signaling molecules, is implicated in the regulation of CNS polarity.Cell. 1993; 75: 1417-1430Abstract Full Text PDF PubMed Scopus (1811) Google Scholar, 4Marigo V. Tabin C.J. Regulation of patched by sonic hedgehog in the developing neural tube.Proc Natl Acad Sci USA. 1996; 93: 9346-9351Crossref PubMed Scopus (259) Google Scholar, 5Stone D.M. Hynes M. Armanini M. Swanson T.A. Gu Q. Johnson R.L. Scott M.P. Pennica D. Goddard A. Phillips H. Noll M. Hooper J.E. de Sauvage F. Rosenthal A. The tumour-suppressor gene patched encodes a candidate receptor for Sonic hedgehog.Nature. 1996; 384: 129-134Crossref PubMed Scopus (968) Google Scholar The SHH gene is expressed in the central nervous system, lung, tooth, gut, and hair follicle.6Goodrich L.V. Johnson R.L. Milenkovic L. McMahon J.A. Scott M.P. Conservation of the hedgehog/patched signaling pathway from flies to mice: induction of a mouse patched gene by Hedgehog.Genes Dev. 1996; 10: 301-312Crossref PubMed Google Scholar, 7Bellusci S. Furuta Y. Rush M.G. Henderson R. Winnier G. Hogan B.L. Involvement of Sonic hedgehog (Shh) in mouse embryonic lung growth and morphogenesis.Development. 1997; 124: 53-63Crossref PubMed Google Scholar, 8Hardcastle Z. Mo R. Hui C.C. Sharpe P.T. The Shh signalling pathway in tooth development: defects in Gli2 and Gli3 mutants.Development. 1998; 125: 2803-2811Crossref PubMed Google Scholar, 9Litingtung Y. Lei L. Westphal H. Chiang C. Sonic hedgehog is essential to foregut development.Nat Genet. 1998; 20: 58-61Crossref PubMed Scopus (578) Google Scholar, 10St-Jacques B. Dassule H.R. Karavanova I. Botchkarev V.A. Li J. Danielian P.S. McMahon J.A. Lewis P.M. Paus R. McMahon A.P. Sonic hedgehog signaling is essential for hair development.Curr Biol. 1998; 8: 1058-1068Abstract Full Text Full Text PDF PubMed Google Scholar IHH is involved in endochondral bone formation,11Vortkamp A. Lee K. Lanske B. Segre G.V. Kronenberg H.M. Tabin C.J. Regulation of rate of cartilage differentiation by Indian hedgehog and PTH-related protein.Science. 1996; 273: 613-622Crossref PubMed Google Scholar and DHH is expressed mostly in gonads.12Bitgood M.J. Shen L. McMahon A.P. Sertoli cell signaling by Desert hedgehog regulates the male germline.Curr Biol. 1996; 6: 298-304Abstract Full Text Full Text PDF PubMed Google Scholar HH proteins undergo a maturation process before their active forms can be secreted from cells and activate HH signaling. The C-terminal domain has proteolytic activity and autocleaves the ligand molecule, generating an N-terminal signaling peptide. This ligand peptide is modified at both ends, esterified with cholesterol moiety at the C-terminal end, and palmitoylated with amide-linked palmitate at the N-terminal end.13Porter J.A. Ekker S.C. Park W.J. von Kessler D.P. Young K.E. Chen C.H. Ma Y. Woods A.S. Cotter R.J. Koonin E.V. Beachy P.A. Hedgehog patterning activity: role of a lipophilic modification mediated by the carboxy-terminal autoprocessing domain.Cell. 1996; 86: 21-34Abstract Full Text Full Text PDF PubMed Scopus (434) Google Scholar, 14Pepinsky R.B. Zeng C. Wen D. Rayhorn P. Baker D.P. Williams K.P. Bixler S.A. Ambrose C.M. Garber E.A. Miatkowski K. Taylor F.R. Wang E.A. Galdes A. Identification of a palmitic acid-modified form of human Sonic hedgehog.J Biol Chem. 1998; 273: 14037-14045Abstract Full Text Full Text PDF PubMed Scopus (590) Google Scholar The bilipidated ligands form multimers, which leave the ligand-producing cell via dispatched (Disp), a 12-transmembrane protein, and are transported via glypicans and megalin to the major cell receptor, patched (Ptc in Drosophila; PTCH in humans).15McCarthy R.A. Barth J.L. Chintalapudi M.R. Knaak C. Argraves W.S. Megalin functions as an endocytic sonic hedgehog receptor.J Biol Chem. 2002; 277: 25660-25667Abstract Full Text Full Text PDF PubMed Scopus (153) Google Scholar The two known human homologs, PTCH1 and PTCH2, are both composed of 12 transmembrane domains and two extracellular loops that have HH ligand binding sites. The PTCH1 gene is located at 9q22.1-q31 and encodes a 1447-amino-acid glycoprotein.16Johnson R.L. Rothman A.L. Xie J. Goodrich L.V. Bare J.W. Bonifas J.M. Quinn A.G. Myers R.M. Cox D.R. Epstein Jr, E.H. Scott M.P. Human homolog of patched, a candidate gene for the basal cell nevus syndrome.Science. 1996; 272: 1668-1671Crossref PubMed Google Scholar The PTCH2 gene is located at 1p34.1 and encodes a 1203-amino-acid protein.17Smyth I. Narang M.A. Evans T. Heimann C. Nakamura Y. Chenevix-Trench G. Pietsch T. Wicking C. Wainwright B.J. Isolation and characterization of human patched 2 (PTCH2), a putative tumour suppressor gene inbasal cell carcinoma and medulloblastoma on chromosome 1p32.Hum Mol Genet. 1999; 8: 291-297Crossref PubMed Scopus (161) Google Scholar PTCH2 and PTCH1 have different intracellular N- and C-terminal domains.18Motoyama J. Takabatake T. Takeshima K. Hui C. Ptch2, a second mouse Patched gene is co-expressed with Sonic hedgehog.Nat Genet. 1998; 18: 104-106Crossref PubMed Google Scholar PTCH1 and PTCH2 are considered to have different functions based on their different expression during development of the epidermis.17Smyth I. Narang M.A. Evans T. Heimann C. Nakamura Y. Chenevix-Trench G. Pietsch T. Wicking C. Wainwright B.J. Isolation and characterization of human patched 2 (PTCH2), a putative tumour suppressor gene inbasal cell carcinoma and medulloblastoma on chromosome 1p32.Hum Mol Genet. 1999; 8: 291-297Crossref PubMed Scopus (161) Google Scholar PTCH1 mutations19Shimkets R. Gailani M.R. Siu V.M. Yang-Feng T. Pressman C.L. Levanat S. Goldstein A. Dean M. Bale A.E. Molecular analysis of chromosome 9q deletions in two Gorlin syndrome patients.Am J Hum Genet. 1996; 59: 417-422PubMed Google Scholar are associated with nevoid basal cell carcinoma syndrome (also known as Gorlin's syndrome, an autosomal dominant disorder characterized by multiple basal cell carcinomas and skeletal defects, among other findings),20Gorlin R.J. Goltz R.W. Multiple nevoid basal-cell epithelioma, jaw cysts and bifid rib A syndrome.N Engl J Med. 1960; 262: 908-912Crossref PubMed Google Scholar medulloblastoma, and meningioma; PTCH2 mutations, although rare, have been reported in medulloblastoma and basal cell carcinoma.17Smyth I. Narang M.A. Evans T. Heimann C. Nakamura Y. Chenevix-Trench G. Pietsch T. Wicking C. Wainwright B.J. Isolation and characterization of human patched 2 (PTCH2), a putative tumour suppressor gene inbasal cell carcinoma and medulloblastoma on chromosome 1p32.Hum Mol Genet. 1999; 8: 291-297Crossref PubMed Scopus (161) Google Scholar In vertebrates, primary cilium is the site where activation of HH signaling occurs. A schematic representation of HH signaling pathway activation is shown in Figure 1. In the absence of HH ligand, PTCH inhibits the smoothened protein (SMO); this protein has seven transmembrane domains, an extracellular N-terminus, and an intracellular C-terminus, with homology to G protein-coupled receptors (GPCRs).21Ogden S.K. Fei D.L. Schilling N.S. Ahmed Y.F. Hwa J. Robbins D.J. G protein Galphai functions immediately downstream of Smoothened in Hedgehog signalling.Nature. 2008; 456: 967-970Crossref PubMed Scopus (166) Google Scholar, 22Philipp M. Caron M.G. Hedgehog signaling: is Smo a G protein-coupled receptor?.Curr Biol. 2009; 19: R125-R127Abstract Full Text Full Text PDF PubMed Scopus (38) Google Scholar Binding of HH ligand to PTCH results in endocytosis of the PTCH-ligand complex, followed by migration of uninhibited SMO to the primary cilium. For localization of SMO to the cilia, a short motif C-terminal to the last transmembrane domain is required.23Corbit K.C. Aanstad P. Singla V. Norman A.R. Stainier D.Y. Reiter J.F. Vertebrate Smoothened functions at the primary cilium.Nature. 2005; 437: 1018-1021Crossref PubMed Scopus (1101) Google Scholar β-Arrestin was reported to mediate this process.24Kovacs J.J. Whalen E.J. Liu R. Xiao K. Kim J. Chen M. Wang J. Chen W. Lefkowitz R.J. Beta-arrestin-mediated localization of smoothened to the primary cilium.Science. 2008; 320: 1777-1781Crossref PubMed Scopus (228) Google Scholar In the cilium, uninhibited SMO transduces the signal to the cytoplasm via intraflagellar transport proteins, with glioma-associated oncogene homolog (GLI) proteins as major targets. The GLI proteins regulate target gene expression by direct association with a consensus binding site located in the promoter region of the target genes.25Sasaki H. Hui C. Nakafuku M. Kondoh H. A binding site for Gli proteins is essential for HNF-3beta floor plate enhancer activity in transgenics and can respond to Shh in vitro.Development. 1997; 124: 1313-1322Crossref PubMed Google Scholar Activation of canonical HH signaling has profound effects on the stability of GLI family of zinc-finger transcription factors. In the absence of HH ligands, the three isoforms of GLI transcription factors (ie, GLI1, 118 kDa; GLI2, 175 kDa; and GLI3, 174 kDa) are ubiquitinated by β-transducin-repeat containing protein (β-TrCP), which is a phosphorylation-dependent E3 ubiquitin ligase. Ubiquitination of GLI proteins requires priming phosphorylations by protein kinase A (PKA), casein kinase 1 (CK1), and glycogen synthase kinase-3β (GSK-3β).26Tempe D. Casas M. Karaz S. Blanchet-Tournier M.F. Concordet J.P. Multisite protein kinase A and glycogen synthase kinase 3beta phosphorylation leads to Gli3 ubiquitination by SCFbetaTrCP.Mol Cell Biol. 2006; 26: 4316-4326Crossref PubMed Scopus (0) Google Scholar, 27Pan Y. Bai C.B. Joyner A.L. Wang B. Sonic hedgehog signaling regulates Gli2 transcriptional activity by suppressing its processing and degradation.Mol Cell Biol. 2006; 26: 3365-3377Crossref PubMed Scopus (426) Google Scholar, 28Huntzicker E.G. Estay I.S. Zhen H. Lokteva L.A. Jackson P.K. Oro A.E. Dual degradation signals control Gli protein stability and tumor formation.Genes Dev. 2006; 20: 276-281Crossref PubMed Scopus (153) Google Scholar After ubiquitination, GLI1 is completely degraded and cleared from the cell by the proteasomal system, whereas GLI2 and GLI3 are partially degraded to form low-molecular weight repressor forms (GLI2R or GLI3R), which migrate to the nucleus, bind to GLI-binding consensus sequences, and repress transcription of HH target genes. For GLI2, however, it was shown that degradation and clearance predominated over formation of the repressor form, which is unlike GLI3 and makes GLI2 more an activator than a repressor of HH signaling.26Tempe D. Casas M. Karaz S. Blanchet-Tournier M.F. Concordet J.P. Multisite protein kinase A and glycogen synthase kinase 3beta phosphorylation leads to Gli3 ubiquitination by SCFbetaTrCP.Mol Cell Biol. 2006; 26: 4316-4326Crossref PubMed Scopus (0) Google Scholar, 27Pan Y. Bai C.B. Joyner A.L. Wang B. Sonic hedgehog signaling regulates Gli2 transcriptional activity by suppressing its processing and degradation.Mol Cell Biol. 2006; 26: 3365-3377Crossref PubMed Scopus (426) Google Scholar, 28Huntzicker E.G. Estay I.S. Zhen H. Lokteva L.A. Jackson P.K. Oro A.E. Dual degradation signals control Gli protein stability and tumor formation.Genes Dev. 2006; 20: 276-281Crossref PubMed Scopus (153) Google Scholar Activation of canonical HH signaling leads to abrogation of phosphorylation-dependent proteolytic degradation of all GLI proteins, increasing their cytoplasmic and nuclear levels and so also increasing transcription of HH target genes: GLI1, PTCH1, PTCH2, BCL2, ABCG2, CCND2, FGF4, VEGFA (previously VEGF), PAX6, PAX7, PAX9, jagged 1 (JAG1), and MYCN, among others. Several regulatory steps control HH pathway signaling. HH-interacting protein (HIP) competes with PTCH for HH binding and attenuates HH signaling.29Chuang P.T. McMahon A.P. Vertebrate Hedgehog signalling modulated by induction of a Hedgehog-binding protein.Nature. 1999; 397: 617-621Crossref PubMed Scopus (632) Google Scholar In mammalian cells, the suppressor of fused protein (SUFU) is a key regulator of the HH pathway, especially at the level of GLI. SUFU inhibits nuclear translocation of GLI proteins by sequestering them in the cytoplasm and thus inhibiting their transcriptional activity.30Monnier V. Dussillol F. Alves G. Lamour-Isnard C. Plessis A. Suppressor of fused links fused and Cubitus interruptus on the hedgehog signalling pathway.Curr Biol. 1998; 8: 583-586Abstract Full Text Full Text PDF PubMed Google Scholar In addition to cytoplasmic sequestration, SUFU also localizes to the nucleus and there suppresses GLI-driven transcription. Nuclear SUFU associates with GLI-binding sites on the DNA and represses gene transcription by recruiting the SAP18-mSin3 complex to GLI promoters.31Cheng S.Y. Bishop J.M. Suppressor of Fused represses Gli-mediated transcription by recruiting the SAP18-mSin3 corepressor complex.Proc Natl Acad Sci USA. 2002; 99: 5442-5447Crossref PubMed Scopus (179) Google Scholar Additional modes of regulating HH signaling include PKA-mediated phosphorylation of GLI1 on residue Thr374, in the vicinity of the nuclear localization sequence, resulting in its cytoplasmic sequestration,32Sheng T. Chi S. Zhang X. Xie J. Regulation of Gli1 localization by the cAMP/protein kinase A signaling axis through a site near the nuclear localization signal.J Biol Chem. 2006; 281: 9-12Abstract Full Text Full Text PDF PubMed Scopus (0) Google Scholar and increased stability and nuclear accumulation of GLI1 induced by GTPase HRas and GTPase NRas via the RAS-RAF-MEK signaling axis.33Stecca B. Mas C. Clement V. Zbinden M. Correa R. Piguet V. Beermann F. Ruiz I Altaba A. Melanomas require HEDGEHOG-GLI signaling regulated by interactions between GLI1 and the RAS-MEK/AKT pathways.Proc Natl Acad Sci USA. 2007; 104: 5895-5900Crossref PubMed Scopus (442) Google Scholar Vertebrate hematopoiesis has two different phases: primitive (embryonic) hematopoiesis and definitive (adult) hematopoiesis. Primitive or embryonic hematopoiesis is characterized by the commitment of embryonic mesoderm to hematopoietic precursors such as embryonic (or primitive) erythrocytes and macrophages.34Keller G. Lacaud G. Robertson S. Development of the hematopoietic system in the mouse.Exp Hematol. 1999; 27: 777-787Abstract Full Text Full Text PDF PubMed Scopus (126) Google Scholar The requirement of IHH in primitive hematopoiesis was established by Dyer et al,35Dyer M.A. Farrington S.M. Mohn D. Munday J.R. Baron M.H. Indian hedgehog activates hematopoiesis and vasculogenesis and can respecify prospective neurectodermal cell fate in the mouse embryo.Development. 2001; 128: 1717-1730Crossref PubMed Google Scholar who showed that IHH ligand secreted by the endoderm was sufficient to induce formation of hematopoietic and endothelial cells. That IHH is a signal playing a key role in the development of the earliest hematovascular system was also supported by another study, in which IHH-deficient embryonic stem cell lines were unable to form blood islands and showed abnormal vascular morphology.36Byrd N. Becker S. Maye P. Narasimhaiah R. St-Jacques B. Zhang X. McMahon J. McMahon A. Grabel L. Hedgehog is required for murine yolk sac angiogenesis.Development. 2002; 129: 361-372Crossref PubMed Google Scholar Definitive hematopoiesis is autonomously initiated with the formation of multipotent hematopoietic stem cells in the aorta-gonad-mesonephros region.37Medvinsky A. Dzierzak E. Definitive hematopoiesis is autonomously initiated by the AGM region.Cell. 1996; 86: 897-906Abstract Full Text Full Text PDF PubMed Scopus (1175) Google Scholar In contrast to primitive hematopoiesis, there is conflicting data regarding the role of HH pathway in definitive hematopoiesis. A study with zebrafish embryo with loss-of-function SHH mutation showed defects in adult hematopoietic stem cell formation.38Gering M. Patient R. Hedgehog signaling is required for adult blood stem cell formation in zebrafish embryos.Dev Cell. 2005; 8: 389-400Abstract Full Text Full Text PDF PubMed Scopus (273) Google Scholar Several other studies have been conducted on the function of SMO in hematopoiesis, but their conclusions are fairly inconsistent. Gao et al39Gao J. Graves S. Koch U. Liu S. Jankovic V. Buonamici S. El Andaloussi A. Nimer S.D. Kee B.L. Taichman R. Radtke F. Aifantis I. Hedgehog signaling is dispensable for adult hematopoietic stem cell function.Cell Stem Cell. 2009; 4: 548-558Abstract Full Text Full Text PDF PubMed Scopus (161) Google Scholar showed that SMO-deficient hematopoietic stem cells were not affected in terms of differentiation, self-renewal, and regeneration of the immune system; they also demonstrated that SMO-deficient hematopoietic stem cells preserved the gene expression signature specific for hematopoietic stem cells. Similar results were observed by Hofmann et al40Hofmann I. Stover E.H. Cullen D.E. Mao J. Morgan K.J. Lee B.H. Kharas M.G. Miller P.G. Cornejo M.G. Okabe R. Armstrong S.A. Ghilardi N. Gould S. DE Sauvage F.J. McMahon A.P. Gilliland D.G. Hedgehog signaling is dispensable for adult murine hematopoietic stem cell function and hematopoiesis.Cell Stem Cell. 2009; 4: 559-567Abstract Full Text Full Text PDF PubMed Scopus (141) Google Scholar and Dierks et al.41Dierks C. Beigi R. Guo G.R. Zirlik K. Stegert M.R. Manley P. Trussell C. Schmitt-Graeff A. Landwerlin K. Veelken H. Warmuth M. Expansion of Bcr-Abl-positive leukemic stem cells is dependent on Hedgehog pathway activation.Cancer Cell. 2008; 14: 238-249Abstract Full Text Full Text PDF PubMed Scopus (457) Google Scholar Zhao et al,42Zhao C. Chen A. Jamieson C.H. Fereshteh M. Abrahamsson A. Blum J. Kwon H.Y. Kim J. Chute J.P. Rizzieri D. Munchhof M. VanArsdale T. Beachy P.A. Reya T. Hedgehog signalling is essential for maintenance of cancer stem cells in myeloid leukaemia [Erratum appeared in Nature 2009, 460:652].Nature. 2009; 458: 776-779Crossref PubMed Scopus (0) Google Scholar however, demonstrated that SMO-deficient mice clearly had a defect in long-term hematopoietic stem cell function in primary and secondary transplants and that therefore SMO is required for hematopoietic stem cell renewal in vivo. More recently, a Gli1null mouse study by Merchant et al43Merchant A. Joseph G. Wang Q. Brennan S. Matsui W. Gli1 regulates the proliferation and differentiation of HSCs and myeloid progenitors.Blood. 2010; 115: 2391-2396Crossref PubMed Scopus (88) Google Scholar showed decreased proliferation of hematopoietic stem cells and myeloid progenitors. Gli1null mice had more long-term hematopoietic stem cells that were more quiescent and showed increased engraftment after transplantation. In contrast, myeloid development was adversely affected, with decreased in vitro colony formation, decreased in vivo response to granulocyte colony-stimulating factor (G-CSF), and impaired leukocyte recovery after treatments with cytotoxic drugs. Results from the Merchant et al43Merchant A. Joseph G. Wang Q. Brennan S. Matsui W. Gli1 regulates the proliferation and differentiation of HSCs and myeloid progenitors.Blood. 2010; 115: 2391-2396Crossref PubMed Scopus (88) Google Scholar study support the notion that GLI1 is a regulator of self-renewal of hematopoietic stem cells and drives myeloid cell proliferation: loss of GLI1 impairs hematopoiesis in situations of stress and impairs the ability to recover after cytotoxic injury or respond to stimulatory cytokines. The thymus is the organ of T-cell development and maturation. In the embryonic stage, progenitor cells are seeded to the thymus from fetal liver; after birth, progenitor cells migrate from the bone marrow to the thymus. In the adult, common lymphoid progenitors enter the blood vessels in the corticomedullary junction or medulla and undergo progressive differentiation of pre-T-cells (thymocytes) as double negative (DN; CD4−CD8−), double positive (DP; CD4+CD8+), and finally single positive (SP; either CD4+CD8− or CD4−CD8+) mature T-cell subsets. The DN stage is further divided into four smaller subsets, based on the expression status of CD25 and CD44: DN1 cells are CD25−CD44+, DN2 cells are CD25+CD44+, DN3 cells are CD25+CD44−, and DN4 cells are CD25−CD44−.44Godfrey D.I. Zlotnik A. Control points in early T-cell development.Immunol Today. 1993; 14: 547-553Abstract Full Text PDF PubMed Google Scholar T-cell lineage specification and T-cell receptor β (TCR-β) rearrangement occur in the DN2 and DN3 stages.45Crompton T. Outram S.V. Hager-Theodorides A.L. Sonic hedgehog signalling in T-cell development and activation.Nat Rev Immunol. 2007; 7: 726-735Crossref PubMed Scopus (117) Google Scholar Pre-TCR signaling is required for survival, proliferation, and differentiation to the DP stage, and is negatively regulated by SHH and IHH signaling.46Outram S.V. Hager-Theodorides A.L. Shah D.K. Rowbotham N.J. Drakopoulou E. Ross S.E. Lanske B. Dessens J.T. Crompton T. Indian hedgehog (Ihh) both promotes and restricts thymocyte differentiation.Blood. 2009; 113: 2217-2228Crossref PubMed Scopus (0) Google Scholar, 47Outram S.V. Varas A. Pepicelli C.V. Crompton T. Hedgehog signaling regulates differentiation from double-negative to double-positive thymocyte.Immunity. 2000; 13 ([Erratum appeared in Immunity 2000, 13:585]): 187-197Abstract Full Text Full Text PDF PubMed Google Scholar, 48Rowbotham N.J. Hager-Theodorides A.L. Furmanski A.L. Ross S.E. Outram S.V. Dessens J.T. Crompton T. Sonic hedgehog negatively regulates pre-TCR-induced differentiation by a Gli2-dependent mechanism.Blood. 2009; 113: 5144-5156Crossref PubMed Scopus (0) Google Scholar, 49Varas A. Sacedón R. Hidalgo L. Martínez V.G. Valencia J. Cejalvo T. Zapata A. Hernández-López C. Vicente A. Interplay between BMP4 and IL-7 in human intrathymic precursor cells.Cell Cycle. 2009; 8: 4119-4126Crossref PubMed Google Scholar, 50Gutiérrez-Frías C. Sacedón R. Hernández-López C. Cejalvo T. Crompton T. Zapata A.G. Varas A. Vicente A. Sonic hedgehog regulates early human thymocyte differentiation by counteracting the IL-7-induced development of CD34+ precursor cells.J Immunol. 2004; 173: 5046-5053Crossref PubMed Google Scholar During transition from DP to SP, both positive and negative selections occur. This developmental program is regulated by the thymic stroma, and one way in which the stroma signals to developing thymocytes is by production of HH ligands. The different components of the HH signaling pathway have been reported to be expressed in the thymus and to play an important role regulating the proliferation and differentiation of thymocytes. HH ligands are produced by stromal, thymic, epithelial, and dendritic cells.46Outram S.V. Hager-Theodorides A.L. Shah D.K. Rowbotham N.J. Drakopoulou E. Ross S.E. Lanske B. Dessens J.T. Crompton T. Indian hedgehog (Ihh) both promotes and restricts thymocyte differentiation.Blood. 2009; 113: 2217-2228Crossref PubMed Scopus (0) Google Scholar, 47Outram S.V. Varas A. Pepicelli C.V. Crompton T. Hedgehog signaling regulates differentiation from double-negative to double-positive thymocyte.Immunity. 2000; 13 ([Erratum appeared in Immunity 2000, 13:585]): 187-197Abstract Full Text Full Text PDF PubMed Google Scholar, 51Sacedón R. Varas A. Hernández-López C. Gutiérrez-deFrías C. Crompton T. Zapata A.G. Vicente A. Expression of hedgehog proteins in the human thymus.J Histochem Cytochem. 2003; 51: 1557-1566Crossref PubMed Google Scholar, 52Varas A. Hernández-López C. Valencia J. Mattavelli S. Martínez V.G. Hidalgo L. Gutiérrez-Frías C. Zapata A.G. Sacedón R. Vicente A. Survival and function of human thymic dendritic cells are dependent on autocrine Hedgehog signaling.J Leukoc Biol. 2008; 83: 1476-1483Crossref PubMed Scopus (0) Google Scholar, 53El Andaloussi A. Graves S. Meng F. Mandal M. Mashayekhi M. Aifantis I. Hedgehog signaling controls thymocyte progenitor homeostasis and differentiation in the thymus.Nat Immunol. 2006; 7: 418-426Crossref PubMed Scopus (87) Google Scholar The fact that thymocytes also express HH ligands (especially IHH in DP-stage thymocytes) was demonstrated by Outram et al.46Outram S.V. Hager-Theodorides A.L. Shah D.K. Rowbotham N.J. Drakopoulou E. Ross S.E. Lanske B. Dessens J.T. Crompton T. Indian hedgehog (Ihh) both promotes and restricts thymocyte differentiation.Blood. 2009; 113: 2217-2228Crossref PubMed Scopus (0) Google Scholar PTCH and SMO are expressed mainly by immature thymocytes. SMO shows a peak expression at DN2, with a decrease in subsequent stages.47Outram S.V. Varas A. Pepicelli C.V. Crompton T. Hedgehog signaling regulates differentiation from double-negative to double-positive thymocyte.Immunity. 2000; 13 ([Erratum appeared in Immunity 2000, 13:585]): 187-197Abstract Full Text Full Text PDF PubMed Google Scholar GLI1 shows the highest expression at DN2 and DN3, then decreases to its minimal level at DP. GLI1 is required for normal differentiation of DN3.54Drakopoulou E. Outram S.V. Rowbotham N.J. Ross S.E. Furmanski A.L. Saldana J.I. Hager-Theodorides A.L. Crompton T. Non-redundant role for the transcription factor Gli1 at multiple stages of thymocyte development.Cell Cycle. 2010; 9: 4144-4152Crossref PubMed Scopus (35) Google Scholar GLI2 is expressed at DN1 and DN2 at the highest level, down-regulated at DN3, and up-regulated at DN4.48Rowbotham N.J. Hager-Theodorides A.L. Furmanski A.L. Ross S.E. Outram S.V. Dessens J.T. Crompton T. Sonic hedgehog negatively regulates pre-TCR-induced differentiation by a Gli2-dependent mechanism.Blood. 2009; 113: 5144-5156Crossref PubMed Scopus (0) Google Scholar The expression of GLI3 is highest at DN1 and DN4 in fetal thymocytes, but is not detected in adult thymocytes. GLI3 is necessary for DN to DP differentiation, especially after pre-TCR signaling.55Hager-Theodorides A.L. Dessens J.T. Outram S.V. Crompton T. The transcrip